Sounds in the Key of Light: Reticence as Soundscape in the Poetry of Arthur Yap - Ching, Lim Lee (SARE: Southeast Asian Review of English, 2017)
In a Singaporean critical landscape that has for much of its short history been concerned with the use of English in its literary culture, Arthur Yap's poetry is notable for its detachment from that kind of consideration, even as he constantly demonstrates the authenticity with which colloquial nuances can be articulated. This is not to say he deliberately writes in defiance of received discourse, stemming from post-colonial linguistic anxities. Rather in Yap's writing, the notion of voice takes precedence over questions of language - not that language, as a poetic topic, is ever far from his thoughts and treatment. With the focus being on the individual's relationship with language, given its immanent complexities and ambiguities, what results is a concentration on the uniqueness with which the individual responds to these qualities of language.